"Perusal of Al-Ghazali’s book "Wisdom in the creatures of God - Al Shibli, Obeida Khalil (Journal of Humanities & Social Sciences, 2018)
The issues of existence and creation are two of the most important themes in the Islamic thought. These two issues encouraged thinkers to write and totally search in its inner meanings and this is the method of Al Emam AL gazaly The book entitled "Alhekme fi maklokat Allah " is one of the most valuable books in the Islamic thinking where it aims to open the way of thinking of the issues of existence and creation. The book is divided into many section , the first one is about the life of Algazali "his name, birth of date and place, his scientific books and writings" .The second section is a study of the different book`s sections highlighting the God wisdom of creating the universe and its parts as "the sun ,the moon ,the earth , the sea , the air ,and the fire ….etc" end then showing the wisdom of creating animals as " ants , bees , spiders ,and silk worm" this section also discusses the reasons that declares the wisdom of creation . the book ends with a conclusion of all that mentioned before subscribed by the whole resources and books.